FORMULATION, OPTIMIZATION, AND CHARACTERIZATION OF BIOCOMPATIBLE INHALABLE D-CYCLOSERINE-LOADED ALGINATE-CHITOSAN NANOPARTICLES FOR PULMONARY DRUG DELIVERY - Shaji, Jessy; Shaikh, Mahmood (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To prepare Nanoparticulate dosage form having improved drug bioavailability and reduced dosing frequency of antitubercular drugs which will helps in improving patient compliance in the treatment of multi-drug resistant tuberculosis (MDR-TB). Methods: Ionotropic gelation method was used to prepare D-cycloserine (D-CS)-loaded alginate-chitosan nanoparticles, and the particles are characterized by their particle size and morphology using particle size analyzer and scanning electron microscopy (SEM). X-ray diffraction (XRD), differential scanning calorimetry (DSC), and Fourier-transformed infrared (FTIR) studies were used to determine drug-polymer interactions and drug entrapment. Entrapment efficiency, drug loading (DL), particle size, and zeta potential of nanoparticles were also studied. The 2 factorial designs of experiments by Design-Expert ® V9 were used to optimize the particle size and entrapment efficiency of nanoparticles. Results: The optimized batch had shown the entrapment efficiency of 98.10±0.24% and DL of 69.32±0.44% with particle size and zeta potential as 344±5 nm and −42±11.40 mV, respectively. DSC, FTIR, and XRD studies confirmed the drug entrapment within nanoparticle matrix. SEM results showed spherical-shaped particles. Sustained release of drug from the nanoparticles was observed for 24 hrs period. Respirable fraction up to 52.37±0.7% demonstrates the formulation suitability for deep lung delivery. Lung inflammatory study showed a less inflammatory response. Conclusion: Ionotropic gelation method can be used to prepare biocompatible particles with a high entrapment efficiency, DL, optimum particle size, and controlled release characteristics, which can serve as a convenient delivery system for D-CS and could be a potential alternative to the existing conventional therapy in MDR-TB. Keywords: Nanoparticles, Alginate, Chitosan, Inhalation, Sustained release, Tuberculosis. 3